Integrating Islamic Economic Values into Islamic Religious Education: An Internalization-Based Learning Model in Secondary Schools - Hendrawan Dwi Saputro; Marselinus Hermawan (MANDALA WIDYA: Jurnal Ilmu Pendidikan, 2026)
This study aims to formulate an Internalization-Based Learning model for Islamic Religious Education (IRE) that integrates Islamic economic values at the secondary school level. The study is grounded in the observed discrepancy between students’ acquisition of religious knowledge and their economic behaviors, which often fail to reflect Islamic ethical principles. A qualitative research and development (R&D) approach was employed, encompassing stages of needs analysis, theoretical synthesis, conceptual model formulation, and expert validation. The findings indicate that the internalization of Islamic economic values becomes effective only when learning is systematically designed to integrate cognitive, affective, and conative dimensions. The proposed model structures the learning process into three main components—input, process, and output—while the stages of value internalization include receiving, responding, valuing, organizing, and characterizing. Core values such as justice (ʿadl), trustworthiness (amānah), and social responsibility are embedded through contextual, reflective, and experiential learning approaches. These findings suggest that Islamic Religious Education should be reconstructed from a mere transmission of knowledge toward a transformative process that shapes students’ economic awareness and behavior. Theoretically, this study contributes to the advancement of Islamic education by integrating Islamic economic perspectives with contemporary learning theories into a unified conceptual framework. Practically, the model has implications for strengthening Islamic financial literacy through more transformative instructional design. However, further empirical testing is required to assess the model’s effectiveness in real-world educational settings.